2016
DOI: 10.3390/pr4030033
|View full text |Cite
|
Sign up to set email alerts
|

Pure Hydrogen Production in Membrane Reactor with Mixed Reforming Reaction by Utilizing Waste Gas: A Case Study

Abstract: A rise in CO2 and other greenhouse gases’ concentration from gas refinery flares and furnaces in the atmosphere causes environmental problems. In this work, a new process was designed to use waste gas (flue gas and flare gas) of a domestic gas refinery to produce pure hydrogen in a membrane reactor. In particular, the process foresees that the energy and CO2 content of flue gas can provide the heat of the mixed reforming reaction to convert flare gas into hydrogen. Furthermore, the characteristics of the feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…These properties, together with high permeability, make such materials very promising for ultra-pure H 2 production in energetic and industrial applications [331]. Nevertheless, several works reported that the H 2 removal fraction never reaches a value higher than 0.80 [305,326,332] for low-to-medium pressures. Besides that, the application of these dense membranes is still limited; for instance, self-supported Pd membranes are considered by several authors not being suitable in MR processes because of their large thickness required for reaching mechanical stability and corresponding low fluxes across the membrane and high costs.…”
Section: Hydrogen Perm-selective Membranesmentioning
confidence: 99%
“…These properties, together with high permeability, make such materials very promising for ultra-pure H 2 production in energetic and industrial applications [331]. Nevertheless, several works reported that the H 2 removal fraction never reaches a value higher than 0.80 [305,326,332] for low-to-medium pressures. Besides that, the application of these dense membranes is still limited; for instance, self-supported Pd membranes are considered by several authors not being suitable in MR processes because of their large thickness required for reaching mechanical stability and corresponding low fluxes across the membrane and high costs.…”
Section: Hydrogen Perm-selective Membranesmentioning
confidence: 99%
“…Recently, some research dedicated to simulate CO 2 conversion in Pd-Ag membrane reformers. [9][10][11][12][13] Jokar et al 14 designed a new process to use domestic gas refinery waste gas to produce pure hydrogen in a membrane reactor. The heat of the reforming reaction was provided by waste energy of flue gas.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that 150 kg/h of hydrogen could be produced in a refinery with 2,500 kg/h of waste gasses. 14 Parvasi et al 4 simulated a recovery loop for reducing CO 2 and greenhouse gas emissions from a gas refinery purge gas. They demonstrated that by assisting a Pd-Ag membrane reactor, the toxic hot gasses could be converted to useful products such as synthesis gas and hydrogen instead of emitting them to the ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…The high abundance of hydrogen, coupled with its high energy density, make it the first candidate to become the energy vector of the next energy transition [1]. Hydrogen can be produced from both fossil and renewable sources [2] [3], but the majority is still derived from fossil reserves. The hydrogen first has to be extracted from the fossil source, then it can be used in a fuel cell to generate electrical power [4] [5].…”
Section: Introductionmentioning
confidence: 99%